2016
DOI: 10.3109/15368378.2016.1141362
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoclast differentiation by static magnetic fields

Abstract: Static magnetic field (SMF) modulates bone metabolism, but little research is concerned with the effects of SMF on osteoclast. Our previous studies show that osteogenic differentiation is strongly correlated with magnetic strength from hypo (500 nT), weak (geomagnetic field, GMF), moderate (0.2 T) to high (16 T) SMFs. We speculated that the intensity that had positive (16 T) or negative (500 nT and 0.2 T) effects on osteoblast differentiation would inversely influence osteoclast differentiation. To answer this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…However, our recent research indicated that the effects of HyMF on bone cannot be overlooked. In vitro, we found that HyMF can inhibit osteoblast differentiation and mineralization, and promote osteoclast formation and bone resorption . In vivo, HyMF aggravated bone loss induced by hindlimb unloading (HLU) in rats and mice .…”
Section: Introductionmentioning
confidence: 92%
“…However, our recent research indicated that the effects of HyMF on bone cannot be overlooked. In vitro, we found that HyMF can inhibit osteoblast differentiation and mineralization, and promote osteoclast formation and bone resorption . In vivo, HyMF aggravated bone loss induced by hindlimb unloading (HLU) in rats and mice .…”
Section: Introductionmentioning
confidence: 92%
“…(a) 9 T static magnetic field makes the Paramecium caudatum move along the direction of magnetic field; (b) the trajectory of Paramecium caudatum in a series of static magnetic fields (i), and the anisotropy of diamagnetic susceptibility were calculated from the relationship between magnetic field and trajectory (ii) [50] ; (c) 8 T static magnetic field causes the Paramecium cilia parallel to the magnetic field, and Ctr is control group [44] 响其与微丝的相互作用. 2017年, Zhang等人 [59] [54] Figure 6 Static magnetic fields affect the self-assembly process of G-actin protein in vitro. (a) Optical micrograph of the G-actin paracrystals in 10 T static magnetic field.…”
Section: 稳态磁场与微丝mentioning
confidence: 99%
“…In contrast, HiSMF (16 T) had a negative effect, which is related with the downregulated expression of osteoclastogenic genes such as matrix metalloproteinase 9 (MMP9), V-ATPase, carbonic anhydrase II (Car2), and RANK. Furthermore, HiSMF altered osteoclast cytoskeleton organization, which destructed the formation of filamentous actin ring and downregulated the expression of integrin β3 [18].…”
Section: Introductionmentioning
confidence: 99%